NMR probe of bulk electronic structures in H+ beam irradiated Bi2Te3 topological insulator - Park, Jun Kue; Lee, Chan Young; Kim, Chorong (Current applied physics, 2019)
We report a nuclear magnetic resonance (NMR) study on H+ beam irradiated Bi2Te3 powdered single crystals. In this work, we demonstrate that the beam creates defects within its penetration range giving rise to delocalized charge carriers, thereby making further 125Te NMR Knight shift and line broadening. Upon increasing temperature, the NMR line narrowing manifests the activated motions of thermally excited charge carriers in the irradiated sample. In contrast, it reveals that in the unirradiated sample the free-charge carriers at the Fermi level dominantly contribute to the Knight shift. Our results show that the orbital contribution to the Knight shift in the bulk state of Bi2Te3 becomes predominant in the system with the higher density of defects, as evidenced by modified electronic structures induced by the beam irradiation. [Display omitted] •Electronic structures of Bi2Te3 are probed by NMR spectroscopy.•H+ beam irradiation leads to modified bulk electronic structures, creating delocalized carriers linked to the Knight shifts.•Orbital contribution in the Knight shift becomes predominant in the Bi2Te3 topological insulator with higher defect levels.